Cross-sectional and longitudinal study protocols of the 'ADIposity and BOne metabolism: effects of eXercise-induced weight loss in obese adolescents' (ADIBOX) project. Issue 10 (18th October 2016) - Chaplais, Elodie; Dutheil, Frédéric; Naughton, Geraldine; Greene, David; Pereira, Bruno; Thivel, David; Courteix, Daniel
Abstract : Introduction: A need exists for sustainable and clinically effective weight management interventions, suitable for preventing well-linked chronic disease such as diabetes and cardiovascular disease and some less investigated secondary conditions such as bone alteration. The ADIposity and BOne metabolism: effects of eXercise-induced weight loss in obese adolescents (ADIBOX) protocol was designed to provide a better understanding of the interaction between adipokines and bone hormones in adolescents with obesity and how a 10-month physical activity programme may affect these interactions. Methods and analysis: The ADIBOX protocol combines 2 studies. The first study involves a total of 68 adolescents aged 12–16 years. This cross-sectional study will include both males and females (1:1 ratio), either living with obesity/overweight (n=34; body mass index (BMI) ≤97th centile and ≥85th centile) or normal weight (n=34; BMI<85th centile). The second study is a longitudinal study that will include 50 obese adolescent girls and track them over a period of 42 weeks. Weight loss programme will consist of a combination of physical activity and a normocaloric diet. Bone and adiposity-related measurements will be performed every 14 weeks. Both studies will assess participants' anthropometric profile, nutrition and physical activity, body composition, bone densitometry and blood markers of bone, growth and adiposity. Ethics and dissemination: The ADIBOX protocol complies with the ethics guidelines for clinical research and has been approved by their respective ethics committee (Australian Catholic University Committee Ethic, Australia and Hospital Sud Est 1 committee, France). Findings from this protocol are expected to clarify the possible interactions between adiposity and bone in childhood obesity and will be disseminated at several research conferences and published articles in peer-reviewed journals. Trial registration number: NCT02626273 ; Pre-results.